Microsaccades and Visual-Spatial Working Memory - Joshua T. Gaunt; Bruce Bridgeman (Bern Open Publishing, 2012)
Observers performed working memory tasks at varying retinal eccentricities, fixating centrally while microsaccade rates and directions were monitored. We show that microsaccades generate no interference in a working memory task, indicating that spatial working memory is at least partially insulated from oculomotor activity. Intervening tasks during the memory interval affected memory as well as microsaccade patterns. Average microsaccade rate peaks after appearance of a fixation cross at the start of a trial, and dips at cue onset and offset. Direction of stimuli in choice tasks did not influence micro-saccade direction, however. Poorer memory accuracy for locations at greater retinal eccentricity calls for revising ideas of short-term spatial representations to include retinotopic or allocentric codes